The Influence of Human Resource Development and Organizational Communication on Employee Performance and Job Satisfaction (Study at PDAM Tirtanadi Medan Sunggal Branch Office) - Zurifa, Rifa; Tahura CH, T. Lyza; Putra, Rizky (Cattleya Darmaya Fortuna, 2023)
The purpose of this study was to analyze the effect of human resource development and organizational communication on employee performance and job satisfaction at PDAM Tirtanadi Sunggal Branch. This type of research is associative research and applies a quantitative approach method using a questionnaire as a means of collecting data which is analyzed with the help of SPSS version 26 software. The population in this study is the number of employees at PDAM Tirtanadi Sunggal Branch, amounting to 120 people. The sampling technique used the Slovin formula method with a total sample of 92 respondents. The data analysis technique used to answer the research hypothesis is regression analysis technique